2009
DOI: 10.1007/s00464-009-0410-x
|View full text |Cite
|
Sign up to set email alerts
|

Society of American Gastrointestinal Endoscopic Surgeons (SAGES) guidelines for office endoscopic services

Abstract: PreambleA number of factors, including reimbursement, have produced a demand for endoscopy to be performed in an office-based setting compared with a hospital or ambulatory center setting. Many gastrointestinal endoscopy procedures can be performed safely in the office setting. To ensure that patients undergoing an endoscopy in an office setting have the appropriate level of safety and quality, standards of care must be set and met. These standards should be similar to, if not the same as, the standards set fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 1 publication
0
37
0
3
Order By: Relevance
“…The RN should be in constant attendance with unrestricted immediate visual and physical access to the patient 1‐3 . While remaining inside the room, the perioperative RN providing moderate sedation/analgesia may perform brief, interruptible, patient‐related, ancillary tasks to assist the perioperative team 1,4‐7 . Examples of brief, interruptible tasks are tying a sterile gown and opening supplies that are in the room when an RN circulator is unavailable.…”
Section: Monitoring Rn Leaving Room During Administration Of Moderatementioning
confidence: 99%
See 1 more Smart Citation
“…The RN should be in constant attendance with unrestricted immediate visual and physical access to the patient 1‐3 . While remaining inside the room, the perioperative RN providing moderate sedation/analgesia may perform brief, interruptible, patient‐related, ancillary tasks to assist the perioperative team 1,4‐7 . Examples of brief, interruptible tasks are tying a sterile gown and opening supplies that are in the room when an RN circulator is unavailable.…”
Section: Monitoring Rn Leaving Room During Administration Of Moderatementioning
confidence: 99%
“…In addition to AORN, the professional organizations supporting the RN performing brief, interruptible tasks are the American Society of Anesthesiologists, the Society of American Gastrointestinal Endoscopic Surgeons, the American Society for Gastrointestinal Endoscopy, the American Academy of Pediatrics, and the Society of Gastroenterology Nurses and Associates 2,4‐7 . The American Association of Nurse Anesthetists and the American Society of PeriAnesthesia Nurses support the RN who is caring for a patient receiving moderate sedation having no other responsibilities during the procedure 9,10…”
Section: Monitoring Rn Leaving Room During Administration Of Moderatementioning
confidence: 99%
“…77,78 The use of NAAP or even NAPS under special circumstances is now recommended by most international guidelines (Table 3). [79][80][81] However, NAAP and NAPS should only be performed where appropriately trained staff, as well as facilities for monitoring and proper airway management, a supply of supplemental oxygen and equipment for advanced cardiac life support are available.…”
Section: Who Should Perform Endoscopic Sedation With Propofol?mentioning
confidence: 99%
“…We also anecdotally observed that occasional patients developed prolonged coughing, postprocedural bronchospasm, unexplained fever, and evidence of pulmonary infection requiring treatment with antibiotics. Such anecdotal cases led us to an approach of meticulous airway protection, including avoidance of deep sedation in patients with acute gastrointestinal bleeding, achalasia, and known delayed gastric emptying [12,13], a policy of vigorous suctioning of the hypopharynx prior to esophageal intubation during upper endoscopy, complete suctioning of the esophagus and stomach prior to examination of the upper GI tract, and careful attention to position change during colonoscopy and to maintaining the availability of oral suctioning to manage reflux during colonoscopy [15]. A study from Italy recently described that 18 of 17,542 patients sedated by Monitored Anesthesia Care during endoscopy required antibiotic treatment for aspiration (0.1%), and that aspiration was a significant contributor to episodes of desaturation [16].…”
Section: Introductionmentioning
confidence: 99%